Surgical Correction of an Extensive Skull Base Defect as a Result of Pneumocele. Issue 1 (January 2016) - Ramprasad, Vaibhav H.; Woodard, Charles R.; Jang, David W.
Abstract : Abstract: Pneumocele is a condition involving the pathologic expansion of paranasal sinuses with corresponding bony erosion of the skull base. Extensive pneumocele can lead to pneumocephalus, especially in patients with long-term cerebrospinal fluid shunts. Here, the authors present a case of pneumocele in an adult with a history of congenital hydrocephalus managed with a ventriculoperitoneal shunt. The patient underwent reconstruction of a posterior table defect with a pericranial flap followed by frontal sinus obliteration with abdominal fat.